Signaling of pigment-dispersing factor (PDF) in the Madeira cockroach Rhyparobia maderae. - Hongying Wei (Public Library of Science (PLoS), 2014)
The insect neuropeptide pigment-dispersing factor (PDF) is a functional ortholog of vasoactive intestinal polypeptide, the coupling factor of the mammalian circadian pacemaker. Despite of PDF's importance for synchronized circadian locomotor activity rhythms its signaling is not well understood. We studied PDF signaling in primary cell cultures of the accessory medulla, the circadian pacemaker of the Madeira cockroach. In Ca²⁺ imaging studies four types of PDF-responses were distinguished. In regularly bursting type 1 pacemakers PDF application resulted in dose-dependent long-lasting increases in Ca²⁺ baseline concentration and frequency of oscillating Ca²⁺ transients. Adenylyl cyclase antagonists prevented PDF-responses in type 1 cells, indicating that PDF signaled via elevation of intracellular cAMP levels. In contrast, in type 2 pacemakers PDF transiently raised intracellular Ca²⁺ levels even after blocking adenylyl cyclase activity. In patch clamp experiments the previously characterized types 1-4 could not be identified. Instead, PDF-responses were categorized according to ion channels affected. Application of PDF inhibited outward potassium or inward sodium currents, sometimes in the same neuron. In a comparison of Ca²⁺ imaging and patch clamp experiments we hypothesized that in type 1 cells PDF-dependent rises in cAMP concentrations block primarily outward K⁺ currents. Possibly, this PDF-dependent depolarization underlies PDF-dependent phase advances of pacemakers. Finally, we propose that PDF-dependent concomitant modulation of K⁺ and Na⁺ channels in coupled pacemakers causes ultradian membrane potential oscillations as prerequisite to efficient synchronization via resonance.